2020
DOI: 10.3201/eid2612.201792
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus Infections and Seroprevalence, Southern Iraq

Abstract: Acute febrile neurological infection cases in southern Iraq (N = 212) were screened for lymphocytic choriomeningitis virus (LCMV). Two LCMV IgM–positive serum samples and 2 cerebrospinal fluid samples with phylogenetically distinct LCMV strains were found. The overall LCMV seroprevalence was 8.8%. LCMV infections are common and associated with acute neurological disease in Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The overall LCMV IgG seroprevalence was 8.8%. In the control group, 12.2% of participants were seropositive compared to 7% in the group of acute febrile patients [ 23 ]. Additionally, LCMV RNA was detected in 5.1% of cerebrospinal fluid samples from patients with a neuroinvasive infection in southern Iraq [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall LCMV IgG seroprevalence was 8.8%. In the control group, 12.2% of participants were seropositive compared to 7% in the group of acute febrile patients [ 23 ]. Additionally, LCMV RNA was detected in 5.1% of cerebrospinal fluid samples from patients with a neuroinvasive infection in southern Iraq [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a previously published Croatian study conducted among inhabitants of the Vir Island showed no gender difference [ 26 ]. In Argentina, significantly higher LCMV seroprevalence was found in men [ 18 , 23 ], while in Canada seroprevalence was higher in women [ 32 ]. The possible reason for this gender distribution is that women are more frequently exposed to dust contaminated with the excreta of house mice during the cleaning of the house and yard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seroprevalence was 12.2% in the healthy control group and 7% in the acute febrile patients. Moreover, two CSF samples from patients with fever and neurologic symptoms were positive for LCMV RNA [26].…”
Section: Lcmv Prevalence In Humansmentioning
confidence: 99%